Quality assurance for antimicrobial susceptibility testing of Neisseria gonorrhoeae in Latin American and Caribbean countries, 2013-2015 - Sawatzky, Pam (2018)
Fil: Sawatzky, Pam. Streptococcus and STI Unit, National Microbiology Laboratory, Public Health Agency of Canada, Winnipeg, Manitoba; Canada.